Kualitas Pelayanan Publik Pada Mall Pelayanan Publik Kota Batam - Indri Amggi Simatupang (Dialektika Publik, 2023)
The reason for making this research is to find out how the performance of employees from public service malls in Batam City in the current era of Regional Autonomy. The mission of the Public Service Mall is to provide convenience, speed, affordability, security and convenience for the community to improve services. In expansion, to strive for the Indonesian state and improve world competitiveness. This research can be a descriptive qualitative research with clear information from observations and social media or the Public Service Mall website. The results of the study indicate that the quality of administration from aspects, among others: system, requirements, specifications of the type of service, and time to prove quite satisfied with the services provided by the Batam City Public Service Mall.